Integrasi Hukum Islam dalam Kebijakan Pengelolaan Sumber Daya Alam: Mencapai Keberlanjutan dan Keadilan Sosial di Indonesia - Susana, Lina Marlina; Tripalupi, Ramadhani Irma; Kholil, Suparman; Efendi, Nur; Sakinah, Gina (Institut Agama Islam Negeri Curup, 2025)
This study examines the integration of Islamic legal principles into Indonesia’s natural resource governance, with a particular focus on sustainability and social justice. The research is motivated by the exploitative and anthropocentric orientation of current policies, which neglect intergenerational equity and ecological justice. To address this gap, the study employs a normative-juridical method with a critical approach, analyzing law as a system of norms rather than merely as social practice. Sources include statutory laws such as the Minerba Law and Job Creation Law, relevant fatwas issued by the Indonesian Council of Ulama, as well as Qur’anic and Hadith texts interpreted through the framework of maqāṣid al-sharī‘ah. Case studies of deforestation in Kalimantan and mining conflicts in West Nusa Tenggara are presented to contextualize the neglect of Islamic values in environmental management. The findings reveal four structural problems: legal dualism between state law and Islamic ethics, weak institutionalization of sharia principles, sectoral fragmentation in governance, and centralization of authority that marginalizes indigenous communities. These issues contribute to the persistent neglect of maslahah, ‘adl, and environmental justice in public policy. The study proposes a maqāṣid-based reconstruction of legal norms through ijtihād maqāṣidī and taḥqīq al-manāṭ as methodological tools to realign governance with ethical and ecological imperatives. Recommendations include revising extractive laws, integrating environmental fatwas into statutory frameworks, strengthening participatory governance, and establishing a Maqāṣid Commission for ecological oversight. In conclusion, the research demonstrates that reconstructing Islamic law through maqāṣid not only fills the ethical gap in Indonesia’s regulatory system but also offers a transformative model for just, participatory, and sustainable environmental governance.